Дискретизация плоской задачи о растяжении тела с трещиной при нелинейном законе деформирования - Хорошун, Л.П. (Прикладная механика, 2010)
A plane problem on tension of a body with crack with piece-wise diagram of deformation is reduced by the Fourier-transform method to the system of nonlinear algebraic equations. The body contains a crack. Basing on numerical solution of the system for the plane strain and stress state of perfect elasto-plastic material, the plastic strain zones, stresses and strains distribution, displacements of crack sides are studied.